2007
DOI: 10.1111/j.1600-0714.2007.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of histopathological and immunohistochemical differences of oral squamous cell carcinoma in young and old patients in Sri Lanka

Abstract: Although tumours of the young patients showed more nuclear aberrations, OSCC of the older patients is proliferative and showed higher metastatic rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
4
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 24 publications
3
39
4
1
Order By: Relevance
“…In the present study, the comparison of OSCC between young and old groups according to three grading systems showed no statistically significant difference (P>0.05). This result was resembles to Sirwardena and Sosaki studies [4,16]. In contrast to our study, Rahman's study showed statistically significant difference between younger and older patients.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…In the present study, the comparison of OSCC between young and old groups according to three grading systems showed no statistically significant difference (P>0.05). This result was resembles to Sirwardena and Sosaki studies [4,16]. In contrast to our study, Rahman's study showed statistically significant difference between younger and older patients.…”
Section: Discussioncontrasting
confidence: 57%
“…However, two groups of Rahman's study have not statistically significant difference based on Broder's criteria, but the young patients have greater aggression of OSCC because differences in nuclear polymorphism, mitosis index and depth of invasion were higher grades among young patients when compared to old patients [2]. In this present study, all individual histopathological parameters was not different statistically significant between two groups (P>0.05), but we found higher nuclear aberrations in the old patients that was contradictory with the results of Siriwardena's study [16]. Furthermore, the results showed the lower host immune response in the younger patients.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…However, an increase in the incidence of head and neck cancer among patients under the age of 45 years has been reported worldwide (4)(5)(6)(7)(8)(9)(10). Some studies suggest that in younger patients, HNSCC arises regardless of the classical risk factors (4)(5)(6)(7)(8)10). HPV infection has been suggested as a possible etiologic factor for such cases (11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…HNSCC comprises malignant epithelial neoplasms that arise in the paranasal sinuses, nasal cavity, oral cavity, pharynx and larynx, and generally affects males between the sixth and ninth decades of life following long-term exposure to smoking and alcohol consumption (3). However, an increase in the incidence of head and neck cancer among patients under the age of 45 years has been reported worldwide (4)(5)(6)(7)(8)(9)(10). Some studies suggest that in younger patients, HNSCC arises regardless of the classical risk factors (4)(5)(6)(7)(8)10).…”
Section: Introductionmentioning
confidence: 99%